2019
DOI: 10.1101/531871
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early Life Adversity, but not suicide, is associated with less prefrontal cortex gray matter in adulthood

Abstract: Background: Suicide and major depression (MDD) are more prevalent in individuals reporting early life adversity (ELA). Prefrontal cortex volume is reduced by stress acutely and progressively in vivo, and changes in neuron and glia density are reported in depressed suicide decedents. We previously found reduced levels of the neurotrophic factor BDNF in suicide decedents and with ELA, and in the present study we sought to determine whether cortex thickness, neuron density or glia density in the dorsolateral pref… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Shrinkage of several cortical structures has also been reported in children who have suffered physical/sexual assault [135,136]. Childhood stress also promotes lasting brain changes beyond youth as retrospective and prospective studies detail how early life adversities can cause the thinning of various cortical structures in adulthood [137][138][139][140][141]. Strikingly, personal experiences of abuse may head brain changes specifically to regions involved with that particular adverse sensory input.…”
Section: Macrostructural Changes In a Stressed Brainmentioning
confidence: 99%
“…Shrinkage of several cortical structures has also been reported in children who have suffered physical/sexual assault [135,136]. Childhood stress also promotes lasting brain changes beyond youth as retrospective and prospective studies detail how early life adversities can cause the thinning of various cortical structures in adulthood [137][138][139][140][141]. Strikingly, personal experiences of abuse may head brain changes specifically to regions involved with that particular adverse sensory input.…”
Section: Macrostructural Changes In a Stressed Brainmentioning
confidence: 99%
“…Stress‐induced molecular and cellular changes in the brain interfere with the normal neurodevelopment, resulting in structural and functional brain alterations. Structural neuroimaging studies have shown that cortical thickness is decreased in people with history of ELA, whereas glial density in PFC and anterior cingulate cortex (ACC) is increased (Underwood et al, 2019). Functional magnetic resonance imaging (fMRI) studies in response to socio‐affective cues found state‐dependent functional changes in the fronto‐limbic and temporo‐parietal areas of the brain in individuals with history of ELA (Heany et al, 2018).…”
Section: Methodsmentioning
confidence: 99%